Literatur Riview : Faktor Risiko Kejadian Laserasi Jalan Lahir pada Kasus Perdarahan Postpartum - Nadilla Afriza; Bella Ardika Maharani; Karlina Karlina; Dona Yebelina (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
This study is a Systematic Literature Review (SLR) which aims to analyze the relationship between risk factors and the incidence of birth canal laceration and its impact on postpartum hemorrhage. The review of various studies showed that postpartum hemorrhage and perineal rupture have complex and interrelated risk factors, with placental retention, uterine atony, and birth canal laceration as the main causes (p-value <0.05). Maternal characteristics such as age, parity (especially in multiparous with a prevalence of 32.9%), history of previous bleeding (OR=7.725), and pregnancy spacing less than two years (OR=6.943) contributed significantly to the risk of complications. Birth weight had a significant association with the incidence of perineal rupture, while the innovative use of warmpad proved effective with 58.8% of cases showing an intact perineum post-delivery. The study also identified anemia in pregnancy as an important risk factor, with the distribution of causes of postpartum hemorrhage including placental retention (44%), uterine atony (28%), uterine rupture (18.6%), and uterine inversion (9.4%), confirming the importance of comprehensive monitoring during pregnancy to prevent complications.